Russia and the 2020 Presidential Election in the United States - Daniela Sandoval Careaga; Alexander Alexeyevich Kornilov (Norteamérica)
Given the outlook for the upcoming 2020 Presidential Election in the United States, where Donald Trump (Republican Party) seeks re-election, and Joe Biden holds the candidacy for the Democratic Party, questions arise regarding how this result may impact Russia in the international scenario. The aim of this analysis is to study that whether Republicans or Democrats win, for Russia the bilateral relationship with the United States -in geopolitical and security terms- will continue to be a challenge. If Trump is re-elected, US foreign policy will follow the line of defensive measures -economic and political-, as well as the retreat of geopolitical spaces and global leadership to guarantee his America First axis. If Biden is elected, Russia will not relax, because the Democrats seek to regain those lost or weakened spaces of leadership. To study this topic, this text will first analyze how Russia places itself in the 21st century, and that is related to its contemporary vision, geopolitical thinking and strategy. Second, from a neorealist perspective, the paper examines what happened in 2016 US Presidential Elections and why it has been alleged to Russian meddling. It is also necessary to go through the key concept of power and how Joseph Nye studies it from a global power shift perspective and how it is related with information technologies, and exploring how it has been related to the so-called Gerasimov Doctrine. Third, the paper continues with the geopolitical scenarios where the US and Russia have interests, agreements and disagreements, since these will help to explain the aim of this work.